ELEMENTS OF GLOACALIZATION IN LATGALIAN MUSIC - Gusāns, Ingars (Via Latgalica, 2016)
Latgalian music has a distinct place within the Latvian music market, which has itself inhabited a niche within the global music marketplace; the various processes of globalization have influenced Latgalian music groups and their members to varying degrees. This article aims to assess which musical styles are most popular amongst Latgalian groups and whether there are parallels with tendencies in the global music world in order to identify which global and local features are typical of Latgalian groups, and describe characteristic Latgalian album design in comparison with that of world-famous groups.The article discusses the following groups: “Borowa MC”, “Bez PVN”, “Dabasu Durovys”, “Laimas Muzykanti”, “Green Novice”, “Sacramental” and Sovvaļnīks. Due to limitations in length, this research does not focus upon text analysis.Research was carried out using the following resources: conversations with group members, internet resources, album reviews, press materials, and the author’s own observations as a member of a Latgalian music group.The research is conducted from a comparative perspective, with the goal of highlighting global and local features that characterize Latgalian groups.According to music critic Sandris Vanzovičs, almost all global music styles are represented in the music of Latgale, each inhabiting their particular niche (Gusāns 2015, 1). Evaluating the musical styles and album packaging of select Latgalian groups, it is possible to conclude that Latgalian groups, in ways that are not connected to dance music, reflect the main global tendencies in music, confirming the global location of the Latgale region. The influence of globalization is noticeable in the English-language names of some groups, e. g. “Green Novice”, “Sacramental”. However, local elements in the music are also present: 1) the use of the Latgalian language, 2) folk song melodies and lyrics used with contemporary interpretations, revealing culturohistorical information, and 3) the desire to design original album covers, trying as much as possible to avoid typical clichés or frequently-used motifs, and highlighting the local area. However, Latgalians still need to overcome the lack of interest or support outside the region for Latgalian music.